Petulangan as a Field of Symbolic Production: Aesthetics, Knowledge, and Hierarchy in the Balinese Funerary Architecture - Anadhi, Made Gede; Suyoga, I Putu Gede (Mudra Jurnal Seni Budaya, 2026)
This article examines the petulangan in Balinese cremation ritual (ngaben) as a material articulation of power, knowledge, and social distinction. Moving beyond symbolic-descriptive interpretations of ritual architecture, the study positions the petulangan as a performative field in which cosmology, hierarchy, and aesthetic production converge. Employing a qualitative interpretive methodology grounded in visual ethnography and discourse analysis, fieldwork was conducted in Gianyar, Bali, involving observation, visual documentation, and interviews with undagi (traditional architects), priests, and customary leaders. The analysis integrates the theoretical frameworks of Michel Foucault’s power–knowledge nexus and Pierre Bourdieu’s concepts of field, habitus, and symbolic capital. From a Foucauldian perspective, the regulation of iconography, proportion, and ritual procedure constitutes a regime of aesthetic orthodoxy through which cosmological truth is stabilized and spiritual legitimacy is disciplined. The petulangan operates as a ritual technology that renders authority visible and socially binding. Through Bourdieu’s lens, cremation aesthetics are understood as a visual economy of distinction, wherein economic, cultural, and social capital are converted into symbolic capital. Monumentality, ornamentation, and artisanal refinement function as strategies of prestige, reproducing social hierarchy through sacred art. The study argues that the petulangan is not merely an ephemeral funerary structure but an active agent in the materialization of cultural politics. Although contemporary economic transformation and commercialization reshape patterns of patronage, the symbolic grammar of hierarchy and cosmological authority remains resilient. Ultimately, Balinese funerary architecture demonstrates how sacred aesthetics simultaneously honour the deceased and reproduce the social order of the living.